P114. Differences in the activation of superficial brain structures by popular dance and art music: An fMRI study. Issue 8 (August 2015) - Rusner, C.; Todt, A.; Knörgen, M.; Spielmann, R.P.; Auhagen, W.
<x xml:space="preserve">Abstract</x> Background Speculations that music might be "moving" not only in metaphorical sense date back to the 17th century. Modern measurement procedures which register activity of the brain could show that not only dancing and playing music, but also listening, and even anticipatory imagination of music may include stimulation of motor areas in the human brain. The aim of this study was to assess the activation of superficial brain structures by popular dance music and art music in young adults using functional magnetic resonance imaging. Methods The recruitment of volunteers for the fMRI experiment was carried out via the social network Stud.IP of the Martin-Luther-University Halle-Wittenberg (http://studip.uni-halle.de/index.php?cancel_login=1). We studied whether there is a difference in activation patterns between 10 subjects who strongly like to dance with frequent visits of music clubs and discos versus 10 subjects who are more or less indifferent towards dancing. The fMRI measurements were performed on a 3.0 Tesla Siemens MAGNETOM Skyra (Erlangen, Germany) at Universitätsklinikum Halle. A block design of popular dance music stimuli, rest, art music stimuli and rest was used in the fMRI experiment. Results With art music, only subjects who are more or less indifferent towards dancing showed activations of superficial brain structures that correspond to the auditory cortex in both hemispheres, as well as homologues of the Wernicke- and Broca-area in the right hemisphere. With popular dance music, both groups of subjects presented cortical activations that correspond to the auditory cortex and the Wernicke-area in both hemispheres. Furthermore, activations of the gyri frontales with the premotor or supplementary motor cortex could be demonstrated. Activations of the cerebellum, especially the vermis, were only observed in subjects who strongly like to dance. Conclusions The results suggest that the attitude towards music and familiarity of certain music genres influence the brain activity.